Opportunistic Nudges for Task Migration Between Personal Devices - Joshi, Nikhita; Li, Richard; Li, Jiannan; Pavanatto, Leonardo; Pahud, Michel; Sharma, Jatin; Lee, Bongshin; Romat, Hugo; Buxton, William; Marquardt, Nicolai; Hinckley, Ken; Henry Riche, Nathalie (Extended Abstracts of the 2024 CHI Conference on Human Factors in Computing Systems (CHI EA '24), 2024)
Using multiple devices to exploit their strengths and mechanics for a task is referred to as “migration.” However, re-establishing context upon moving from one device to another can be cumbersome. We propose opportunistic nudges as a way to more seamlessly share content between personal devices. Opportunistic nudges appear in the bezel when a device migration occurs and can be interacted with to quickly share files and applications. However, if the user ignores them, they automatically disappear after some time. We explore the design space of opportunistic nudges through rapid prototyping and develop a preliminary design space consisting of four stages. Focusing on six design parameters of the Visualization stage, we gather feedback on the concept through an exploratory user study. Results show that opportunistic nudges can be an effective way to reduce the transaction costs of sharing content between devices.